2014
DOI: 10.1186/1471-2407-14-910
|View full text |Cite
|
Sign up to set email alerts
|

Modification of topoisomerases in mammospheres derived from breast cancer cell line: clinical implications for combined treatments with tyrosine kinase inhibitors

Abstract: BackgroundAccumulating evidences suggest that tumors are driven by a small population of cells, termed “cancer stem cells” (CSCs), which may be resistant to current therapeutic approaches. In breast carcinoma, the CSCs have been identified as a CD44+/CD24− cell population. These rare cells are able to grow as non-adherent sphere-like structures, termed “mammospheres”, which enables their isolation and expansion in culture. To design efficient strategies for the complete eradication of CSCs, it is important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…At present, the sorting methods of CSCs include flow cytometry based on special cell surface markers, the side population cell sorting technique, tumor sphere culturing and the ALDEFLUOR™ assay (6)(7)(8)(9). Previous studies have identified the CSCs from colon, breast and glioblastoma cancer, as well as other cancer cell lines, using the sphere culturing method (10)(11)(12). Tumor cell sphere culturing may be a convenient method for generating cancer stem-like cells to be used in the research of malignant behavior.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the sorting methods of CSCs include flow cytometry based on special cell surface markers, the side population cell sorting technique, tumor sphere culturing and the ALDEFLUOR™ assay (6)(7)(8)(9). Previous studies have identified the CSCs from colon, breast and glioblastoma cancer, as well as other cancer cell lines, using the sphere culturing method (10)(11)(12). Tumor cell sphere culturing may be a convenient method for generating cancer stem-like cells to be used in the research of malignant behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Located at the top of the tumor hierarchy, CSC can self‐renew and generate non‐CSC progeny that form the tumor bulk (differentiated progeny) . Additionally, CSC has been suggested to account for tumor growth, progression, metastatic capacity, and therapy resistance . Our results showed that the compounds assessed acted in different ways in monolayer and tumorsphere models.…”
Section: Discussionmentioning
confidence: 82%
“…MPA and Gefitinib are effective drugs in breast and endometrial cancer therapy [ 12 , 26 ]. Moreover, Gefitinib is an effective drug in therapy for prostate, gastric, colorectal and non-small cell lung cancers [ 27 30 ]. Our data demonstrates that Gefitinib enhances anti-tumor properties of MPA via DUSP1 in EC cells, both in-vitro and in-vivo .…”
Section: Discussionmentioning
confidence: 99%